2019
DOI: 10.1108/joepp-10-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

A unified model of organizational effectiveness

Abstract: Purpose Scholars for long have been interested in finding effective ways to assess organizational effectiveness. However, lack of consensus on its definition, and consequently on measure parameters has dogged researchers, almost to the point that some academics have declared organizational effectiveness a subject that cannot be researched. The purpose of this paper is to present a unified model of organizational effectiveness by recognizing the underlying synergy in the body of research – a framework that coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 86 publications
0
11
0
1
Order By: Relevance
“…It derives from the ability to solve problems, implement valuable strategies, create new services, and develop new processes in order to analyze and meet customers that explicitly affect firms' great competitiveness, profitability and performance. In achieving organizational effectiveness, healthy financial organization, external confidence in the organization, efficient and reliable organizational processes, and employee's confidence in the organization have become indicators of firms' effectiveness in market competition growth (Sharma & Singh, 2019). Likewise, organizational effectiveness is defined as how a firm accomplishes its tasks effectively.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…It derives from the ability to solve problems, implement valuable strategies, create new services, and develop new processes in order to analyze and meet customers that explicitly affect firms' great competitiveness, profitability and performance. In achieving organizational effectiveness, healthy financial organization, external confidence in the organization, efficient and reliable organizational processes, and employee's confidence in the organization have become indicators of firms' effectiveness in market competition growth (Sharma & Singh, 2019). Likewise, organizational effectiveness is defined as how a firm accomplishes its tasks effectively.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
“…Likewise, some studies have shown that strategic management accounting may not directly lead to firm performance, but it needs to have mediators that help link to firm performance. Accordingly, this study has proposed operational excellence, managerial efficiency and organizational effectiveness as the mediators of the study (Chang & Ma, 2019;Sharma & Singh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The modern business environment creates challenges for managers to play their leadership role responsibly and to uphold a productive workforce (Haque et al , 2019c, 2020; Sharma and Singh, 2019). One significant way to support a productive workforce is managerial leadership, through which managers inspire, involve and motivate their employees (Suriyankietkaew and Avery, 2014; DeArmond et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, the deployment of talent management leads to organizational effectiveness. There is, however, a need to contextualize what organizational effectiveness measures are due to divergence of opinions (see for example Sharma & Singh, 2019;Uche & Timinepere, 2012;Tofighi, Chaghary, Amerioun & Zarchi, 2011), on what OE is and what the organizational effectiveness indicators are. Although there are five transformational leadership dimensions, only four are popular, idealized behaviours, inspirational motivation, intellectual stimulation and individualized consideration Extant literature revealed that some studies have conceptualized idealized influence attribute and idealized influence behaviours as idealized influence (Hoxha, 2015;Ahmad, Mohamed & Manaf, 2017;Cahyono, Novitasari, Sihotang, Aman, Fahlevi, Nadeak & Purwanto, 2020;Mukhtar, Risnita & Prasetyo, 2020).…”
Section: Issues Arising From Conceptual Reviewmentioning
confidence: 99%